2021
DOI: 10.36740/abal202104105
|View full text |Cite
|
Sign up to set email alerts
|

Means of police Officers’ physical and psychological Rehabilitation in the Conditions of their service Activities

Abstract: Aim: To determine the negative factors of police of f i cers’ service activities and to theoretically substantiate the available means of police officers' physical and psychological rehabilitation in the conditions of their service activities. Materials and methods: To analyse the peculiarities of police service activities, we conducted the survey of police officers (n=237) of various structural units of the National Police of Ukraine. The expert assessment was conducted in order to determine the effective mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…In addition, our research confirmed our earlier opinion that successful police officers are characterized by controlled behavior, selfcontrol, perseverance, diligence, thoroughness, responsibility, discipline, a low level of neuroticism, the absence of depressive and hypochondriac tendencies, etc. (Aleksandrov et al, 2017;Bondarenko et al, 2021;Miloradova et al, 2022;Ponomarenko et al, 2022).…”
Section: Limits and Discussionmentioning
confidence: 99%
“…In addition, our research confirmed our earlier opinion that successful police officers are characterized by controlled behavior, selfcontrol, perseverance, diligence, thoroughness, responsibility, discipline, a low level of neuroticism, the absence of depressive and hypochondriac tendencies, etc. (Aleksandrov et al, 2017;Bondarenko et al, 2021;Miloradova et al, 2022;Ponomarenko et al, 2022).…”
Section: Limits and Discussionmentioning
confidence: 99%